QUALITATIVE CHARACTERISTIC OF FINANCIAL STATEMENT INFORMATION AND IMPLEMENTATION PSAK 73 : CASE STUDY IN THE ADVERTISING SERVICES PT ABC - Hasnawati, Hasnawati; Marsdenia, Marsdenia; Salsabila, Trie Wiesty Cindy (Jurnal Vokasi Indonesia, 2024)
The quality of information presented in the financial statement is the most important thing for stakeholders in the business decision-making context. There has been a significant change in lease accounting practices due to changes in lease accounting standards for all business entities in countries that adopt IFRS. In 2017 the IASB published IFRS 16 Leases as new guidance on leases replacing IAS 17. DSAK IAI made adjustments related to IAS 17 to become PSAK 30, then based on the changes that emerged PSAK 30 was revoked and adjustments were made to IFRS 16 to become PSAK 73. These changes were based on to goal to comply with the qualitative characteristics of financial statements, Additionally. the lack of reflection of company performance in financial reports due to lease classification based on PSAK 30. This is a Qualitative method by using literature study, document, observation, and interview with key informants. The research object is advertising agency PT ABC. This study concluded that PT ABC accounting on the leasing transactions complies with PSAK 73, which its applications have implications in financial statements by comparing it using PSAK 30. The results of the objects the author examined show that PT ABC implemented PSAK 73 for its leasing transactions following the regulations in force in 2020 and 2021. Next related PT ABC's company performance has increased in all the ratios studied. The increase that appeared in the DER and DAR ratios was due to the disclosure of right-of-use assets and finance lease liabilities in the financial statements and then the increase that appeared in the ROA and ROE ratios was due to an increase in the company's loss/profit for the current.